Bridging HPLC‐ESI‐MS/MS analysis and in vitro biological activity assay through molecular docking and network pharmacology: The example of European nettle tree (Celtis australis L.) - Mehmet Veysi Cetiz; Sakina Yagi; Umran Kurt; Ismail Koyuncu; Ozgur Yuksekdag; Giovanni Caprioli; Laura Acquaticci; Simone Angeloni; Ismail Senkardes; Gokhan Zengin (eFood)
Abstract Celtis australis L. (Family: Cannabaceae) is commonly used to treat many diseases like gastrointestinal problems, menstrual bleeding and amenorrhea. The present study was designed to investigate the chemical constituents, antioxidant, enzyme inhibitory and cytotoxic properties of different extracts from twigs, fruits and leaves of C. australis. EtOAc, EtOH, 70% EtOH and aqueous extracts were prepared by maceration. Results showed that the EtOH extract of the leaves had the highest total phenolic content and possessed remarkable antiradical, ion reducing and total antioxidant activities. Additionally, the leaves (EtOH or EtOAc extracts) exerted the best enzyme inhibition properties. The polar extracts of the leaves had significant cytotoxic effect against the human colorectal adenocarcinoma (HT‐29) and human prostate cancer (DU‐145) cell lines while the EtOAc of the twigs was effective against the former cell line. Phytochemically, the twigs and fruits accumulated high content of vanillic acid, 4‐hydroxy benzoic acid and syringic acid. Through a combination of in vitro and in silico approaches, we identified key phytochemicals exhibited significant inhibitory effects on several cancer‐related proteins, through in vitro and in silico approaches that show significant inhibition of cancer‐related proteins. In conclusion, these findings indicated that C. australis could be a promising source of bioactive molecules for food, pharmaceutical and cosmetic industries.